ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN PROFIL DEWAN DIREKSI TERHADAP KUALITAS AUDIT - Mardianto; Junifa (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research aims to analyze the effect of corporate governance and the profile of the board of directors on the quality of audits that will be produced by companies listed on the IDX. The dependent variable used is audit quality (dummy variable). The data obtained will be tested using logistic regression analysis with SPSS 25 application. The results showed that female directors, age of the board of directors, expertise of the board of directors, size of the board of directors, independence of the board of directors, independent audit committee, and audit committee meetings did not have a significant effect on audit quality. Meanwhile, audit committee size has negative significant effect on audit quality. And board of directors meeting, firm size and firm age have a significant positive effect on audit quality. All independent variables can explain the dependent variable as much as 41.7%.